THE COMPUTATIONAL TOOLS INTERNET OF THINGS, BIG DATA, DATA MINING AND THE ENERGY EFFICIENCY - Vasconcelos, J. S.; Barreiros, R. M.; Zuin, L. F. S.; Rabi, J. A.; Baesso, M. M.; Godinho, E. Z.; Caneppele, F. L. (Revista Brasileira de Engenharia de Biossistemas, 2019)
Computer science is a tool that has allowed great advances for the development of humanity in recent decades, leading to well-being, productivity and various types of gains. In turn, with the increasing consumption of electric energy, energy efficiency has been used by more areas and sectors of society. This work aims to investigate the literatures and terminologies of Internet of Things, Big Data, Data Mining and the relationship with energy efficiency through publications and application examples these terms. A literature review was carried out based on the search for works in the area of computing and computing and its relation with energy efficiency. Considering that these themes are contemporary to the new millennium, even though the themes are recent and although several items still need to be deepened, there is a great development involving energy efficiency and the terms internet of things, great data and data mining.